1998
DOI: 10.1107/s0907444998004284
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and Discontinuous Changes in the Unit Cell of HIV-1 Reverse Transcriptase Crystals on Dehydration

Abstract: A crystal form of HIV-1 reverse transcriptase (RT) complexed with inhibitors showed diffraction to a highresolution limit of 3.7 ,~. Instability in the unit-cell dimensions of these crystals was observed during soaking experiments, but the range of this variability and consequent change in lattice order was revealed by a chance observation of dehydration. Deliberately induced dehydration results in crystals having a variety of unit cells, the best-ordered of which show diffraction to a minimum Bragg spacing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 31 publications
2
61
0
1
Order By: Relevance
“…Contrary to dehydration (Esnouf et al, 1998), variations in salt concentration cause small changes in the unit-cell parameters and volume within 0.3±0.4 A Ê and 1%, respectively (Fig. 2c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to dehydration (Esnouf et al, 1998), variations in salt concentration cause small changes in the unit-cell parameters and volume within 0.3±0.4 A Ê and 1%, respectively (Fig. 2c).…”
Section: Discussionmentioning
confidence: 99%
“…Higher order in protein crystals has been achieved either by crystal dehydration or post-crystallization soaking in solutions containing stabilizing agents such as glycerol and polyols (Sousa, 1995). By monitoring the changes in the unit cell of HIV-1 reverse transcriptase crystals during controlled dehydration, Esnouf et al (1998) managed to successfully determine conditions which improved the resolution from 3.7 to 2.2 A Ê . Earlier, an improvement in diffraction as a result of crystal partial dehydration was observed in crystals of a complex between cytochrome c and cytochrome c peroxidase (Pelletier & Kraut, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Below 86% r.h. the diffraction quality deteriorated and the process was not reversible. This is reminiscent of the complex dehydration behaviour observed in HIV-1 reverse transcriptase crystals (Esnouf et al, 1998). WbdD556 crystals often cracked during dehydration with the FMS, degrading the diffraction quality.…”
Section: Figurementioning
confidence: 99%
“…Use of electron density as a molecular-replacement model with, for example, PHASER (McCoy et al, 2007) is now much more automated and this was also critical to our success. Although multiple cases are known in which crystals were successfully dehydrated to improve their diffraction properties (see, for example, Esnouf et al, 1998;Kiefersauer et al, 2000;Chotiyarnwong et al, 2007), it is still a technique that is rarely reported. This perhaps reflects frequent failure or technical difficulties.…”
Section: Effect Of Dehydration On the Structurementioning
confidence: 99%
“…In addition, it is fairly common that crystals of large macromolecular complexes such as the ribosome suffer from a lack of isomorphism on cryo-cooling. This apparent problem could be exploited to provide a vehicle for phasing such complexes, because of the differential sampling of the molecular transform which occurs on changes in the unit cell (Esnouf et al, 1998;Ren et al, 1995). Thus, EM reconstructions could provide starting models for each of the crystal forms and would establish initial values for the rotation matrices and translation vectors which relate the molecules in the different forms prior to non-crystallographic averaging between them.…”
Section: Prospects For the Futurementioning
confidence: 99%